Pathogenesis of influenza virus-induced pneumonia: involvement of both nitric oxide and oxygen radicals. - Akaike, T (1996)
The role of nitric oxide (NO) in the pathogenesis of influenza virus-induced pneumonia in mice was investigated. Experimental influenza virus pneumonia was produced with influenza virus A/Kumamoto/Y5/67(H2N2). Both the enzyme activity of NO synthase (NOS) and mRNA expression of the inducible NOS were greatly increased in the mouse lungs; increases were mediated by interferon gamma. Excessive production of NO in the virus-infected lung was studied further by using electron spin resonance (ESR) spectroscopy. In vivo spin trapping with dithiocarbamate-iron complexes indicated that a significant amount of NO was generated in the virus-infected lung. Furthermore, an NO-hemoglobin ESR signal appeared in the virus-infected lung, and formation of NO-hemoglobin was significantly increased by treatment with superoxide dismutase and was inhibited by N(omega)-monomethyl-L-arginine (L-NMMA) administration. Immunohistochemistry with a specific anti-nitrotyrosine antibody showed intense staining of alveolar phagocytic cells such as macrophages and neutrophils and of intraalveolar exudate in the virus-infected lung. These results strongly suggest formation of peroxynitrite in the lung through the reaction of NO with O2-, which is generated by alveolar phagocytic cells and xanthine oxidase. In addition, administration of L-NMMA resulted in significant improvement in the survival rate of virus-infected mice without appreciable suppression of their antiviral defenses. On the basis of these data, we conclude that NO together with O2- which forms more reactive peroxynitrite may be the most important pathogenic factors in influenza virus-induced pneumonia in mice.